2008
DOI: 10.4049/jimmunol.181.3.1887
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Possesses Powerful Immunomodulatory Activity and Suppresses Experimental Autoimmune Encephalomyelitis

Abstract: Bilirubin, an abundant bile pigment in mammalian serum, was once considered a toxic waste product and has more recently been recognized as a potent antioxidant of physiological importance. However, its potential biological functions in other fields are not well understood. Herein we show that bilirubin is also a powerful immunomodulatory agent. Bilirubin significantly inhibited Ag-specific and polyclonal T cell responses, while other similar antioxidants completely lacked this effect. Bilirubin suppressed CD4+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
168
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(179 citation statements)
references
References 42 publications
8
168
1
2
Order By: Relevance
“…Previous evidence had shown that UCB has immunomodulatory properties in inflammatory conditions in vivo (2,6). We tested the effect of UCB administration on DSS-induced colitis during the induction and recovery phases of the disease, when the DSS treatment was replaced with standard drinking water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence had shown that UCB has immunomodulatory properties in inflammatory conditions in vivo (2,6). We tested the effect of UCB administration on DSS-induced colitis during the induction and recovery phases of the disease, when the DSS treatment was replaced with standard drinking water.…”
Section: Resultsmentioning
confidence: 99%
“…High systemic concentrations of UCB in certain disease states are potentially injurious to the basal ganglia and neurons (1). However, physiological concentrations of this metabolite have immunomodulatory effects on antigen-presenting cells (2,3) and effector cells (2,4), ultimately favoring the expansion of FOXP3 + Tregs (5,6). UCB immunomodulatory properties have been confirmed by in vivo experimental studies, as in the setting of islet cell transplantation (6,7), experimental autoimmune encephalomyelitis (2), and in acute colitis induced by dextran sodium sulfate (DSS) (8).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors pointed out that bilirubin is likely to play important physiological functions because biliverdin is water soluble and could be directly excreted. It was already shown that bilirubin has antioxidant [51] and immunomodulatory [52] functions. Bilirubin diglucuronide is a sign of liver injury; biliverdin diglucuronide is possibly an oxidation product of bilirubin diglucuronide reflective of liver injury [53].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid release of bilirubin into the blood may also be as a result of obstruction of bile ducts or damage to the liver cells, so that even the usual amounts of bilirubin cannot be excreted into the gastrointestinal tracts. The elevated level observed may indicate liver damage or disease (22).…”
Section: Resultsmentioning
confidence: 99%